2011
DOI: 10.1634/theoncologist.2011-0150
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Controlled Study of the Botanical Compound Mixture LCS101 for Chemotherapy-Induced Hematological Complications in Breast Cancer

Abstract: Background. This prospective, controlled study evaluated the safety, tolerability, and efficacy of the mixture of botanical compounds known as LCS101 in preventing chemotherapy-induced hematological toxicity in breast cancer patients.Methods. Female patients diagnosed with localized breast cancer were randomly allocated to receive treatment with either LCS101 or placebo capsules, in addition to conventional chemotherapy. The study intervention was initiated 2 weeks prior to the initiation of chemotherapy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…In conclusion, Yaal-Hahoshen et al [1] claimed that the addition of LCS101 to conventional chemotherapy is safe and feasible in patients with early breast cancer. However, their study lacks essential information regarding the hematoprotective mechanism of action of LCS101, potential PK interactions with chemotherapy, and the PD effects of LCS101 on the tumor.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…In conclusion, Yaal-Hahoshen et al [1] claimed that the addition of LCS101 to conventional chemotherapy is safe and feasible in patients with early breast cancer. However, their study lacks essential information regarding the hematoprotective mechanism of action of LCS101, potential PK interactions with chemotherapy, and the PD effects of LCS101 on the tumor.…”
mentioning
confidence: 90%
“…Based on the results of a prospective, randomized, placebocontrolled study of Yaal-Hahoshen et al, [1] the authors concluded that the botanical mixture LCS101 prevented hematological complications in breast cancer patients undergoing anthracycline-and taxane-based chemotherapy. They also concluded that the addition of LCS101 to conventional chemotherapy regimens "is both safe and feasible in patients with early breast cancer, .…”
mentioning
confidence: 99%
See 3 more Smart Citations